COLORED AREA, GROWTH-RING WIDTH, AND LATEWOOD PERCENTAGE IN HYBRID PINE F1 INTA-PINDO - Winck, Rosa Angela; Winck, Lucía Raquel; Belaber, Ector César; Aquino, Diego Rolando; Area, María Cristina; Gauchat, María Elena (Floresta, 2023)
The characteristics of the annual growth rings are indicators of the growth and quality of the wood. At 11 years of age, 90 F1 hybrid pine trees of Pinus elliottii x Pinus caribaea var. hondurensis were sampled from two sites. The sample consisted of 15 families and 3 positions in the genetic growth ranking. Disks were taken at 0.10 m, 1.30 m, and 4.45 m, colored area (%) in the central zone of the log, ring width, growth-ring area, and proportion of latewood were evaluated. The data were analyzed with mixed linear models. Statistically significant differences were found between families for the studied variables, except for latewood percentage. Family 02 showed higher growth and a low proportion of pink core. Families 01 and 03 had a higher percentage of colored area. The percentage of colored area increased with tree height. The ring width decreased with tree height and was higher for families 01, 02, 03, 04, 05, and 07. The latewood percentage increased from the pith to the bark and from the tree base to the crown. To conclude, top-growth families exhibited higher mean ring width and ring area than lower-growth families but the same proportion of latewood. These are desirable characteristics for obtaining wood quality for structural uses.